Nerve Conduction Study of Newly Diagnosed Type 2 Diabetic Patients and Its Correlation with Glycosylated Hemoglobin (HbA1c) (Bangladesh Journal of Neuroscience, 2026)
Background: Peripheral neuropathy is one of the common complications of DM and may proceed by a long period of clinically silent impaired glucose tolerance, altering the nerve function by the time diabetes is diagnosed. Nerve conduction (NCS) remainthe most reliable, accurate and sensitive measure for diagnosis of peripheral neuropathy. Objectives: Evaluation of nerve conduction study of newly diagnosed type -2 diabetic patients and to find out its correlation with glycosylated hemoglobin (HbA1c). Method: This is a case control study. A total 50 newly diagnosed type-2 diabetic patients within 1 month of both sex and another 50 healthy controls were studied prospectively during January 2018 to December 2019 from outpatient department of Endocrinology and advised to attend the department of Neurology of Dhaka medical college hospital. Nerve conduction study of cross limbs was performed. Blood sugar and glycosylated hemoglobin (HbA1C) were determine.Results: Motor nerve conduction parameters were more affected. Median nerve impairment in both motor and sensory nerve conduction study was statistically significant (p10%. Combination tibial and peroneal nerve involvements were more common 11 (22.0%), followed. In multivariate regression analysis, HbA1C significantly (p